Investigation of lifting force affected by the velocity and Angle of Attack (AoA) In Wing-in-Ground (WiG) craft - Mohd Rasidi, Ibrahim; Aishah, Ahmad; Radzman Hakim, Taufek; Suhaimi, Hassan; M. Zulafiff, Rahim; Juita Mastura, Mohd Salleh; Omar Mohd Faizan, Marwah; Zamri, Omar; Fareza, Fazidi; Razali, Abidin; Saiful Anwar, Che Ghani (Semarak Ilmu Publishing, 2024)
The Wing-in-Ground (WIG) craft represents a pioneering vehicular innovation that exploits aerodynamic lift via a cushioning mechanism, enabling it to remain suspended above the water's surface. A notable concern encountered during the navigational manoeuvres of the WIG craft over the uneven sea terrain pertains to its potential impact on fuel efficiency during flight durations. This research objective is focused on the pivotal of ascertaining the optimal lifting force prerequisites for a prototype WIG craft. This comprehensive study entails an exploration of diverse combinations of velocities and angles of attack (AoA) to identify the most suitable configuration capable of attaining the requisite lift force levels. The study's methodology revolves around the adaptation of the actual WIG concept, encompassing a focus on the aerofoil profile and leveraging insights garnered from a design concept pertaining to WIG craft. To emulate real-world scenarios with precision, computational simulations employing the flow simulation capabilities of SolidWorks software are executed concurrently with the validation of a fabricated prototype. Parameters encompassing, angle of attack, and velocity are meticulously configured, adhering to the commonly employed parameters within the realm of WIG craft operations. The resulting outcomes are rigorously validated and subsequently compared against a lift coefficient of 1.25 at an angle of attack set at 16°, consistent with outcomes from prior research activities. This established angle of attack serves as a foundational reference for the present study's empirical conclusions. The culmination of these simulations yields the identification of an optimal arrangement characterized by a velocity of 120 km/h coupled with an angle of attack measuring 20°. This particular configuration consistently stimulates the requisite magnitude of lift force, thereby demonstrating the feasibility of elevating the WIG craft prototype without compromising stability or safety.